Etruscology - Naso, Alessandro (De Gruyter reference., 2017)
This handbook has two purposes: it is intended (1) as a handbook of Etruscology or Etruscan Studies, offering a state-of-the-art and comprehensive overview of the history of the discipline and its development, and (2) it serves as an authoritative reference work representing the current state of knowledge on Etruscan civilization. The organization of the volume reflects this dual purpose. The first part of the volume is dedicated to methodology and leading themes in current research, organized thematically, whereas the second part offers a diachronic account of Etruscan history, culture, religion, art & archaeology, and social and political relations and structures, as well as a systematic treatment of the topography of the Etruscan civilization and sphere of influence.